DEVELOPMENT OF INTERACTIVE EDUCATIONAL MULTIMEDIA USING CANVA FOR THE TOPIC OF SYSTEM OF LINEAR INEQUALITIES IN TWO VARIABLES FOR 10TH GRADE - Gitami Suleman; Hasan S. Panigoro; Taulia Damayanti (Universitas Cokroaminoto Palopo, 2026)
This study aims to develop a Canva-based interactive multimedia published as a website multimedia learning tool on the topic of System of Linear Inequalities in Two Variables that is suitable for use in the mathematics learning process. This study employs the Research and Development (R&D) method using the ADDIE development model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The analysis stage involved identifying needs, learner characteristics, the curriculum, content, as well as the learning environment and resources. The design stage included formulating learning objectives, designing the presentation flow, user interface, storyboard, and research instruments. Subsequently, in the development stage, a website-based educational multimedia was created and validated by subject matter experts and media experts. The results of the study indicate that the developed educational multimedia meets the feasibility criteria and can be used in the learning process. This educational multimedia is expected to help students understand the material more easily and increase their interest in the learning process.